2011
DOI: 10.1074/jbc.m110.188581
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans Galectins LEC-6 and LEC-10 Interact with Similar Glycoconjugates in the Intestine

Abstract: Galectins are a family of metazoan proteins that show binding to various β-galactoside-containing glycans. Because of a lack of proper tools, the interaction of galectins with their specific glycan ligands in the cells and tissues are largely unknown. We have investigated the localization of galectin ligands in Caenorhabditis elegans using a novel technology that relies on the high binding specificity between galectins and their endogenous ligands. Fluorescently labeled recombinant galectin fusions are found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…15) Our present results are consistent with, and support to their observation; that is, we also found LEC-6 interacts with F57F4.3/4 protein in vitro, and furthermore, presented a evidence that the interaction between these The worms were fed with equal amount of E. coli expressing double-stranded RNA targeted to indicated genes, or mock. Feeding was begun at the L4 stage.…”
Section: Identification Of F57f44 As a Major Glycoprotein Counterparsupporting
confidence: 92%
“…15) Our present results are consistent with, and support to their observation; that is, we also found LEC-6 interacts with F57F4.3/4 protein in vitro, and furthermore, presented a evidence that the interaction between these The worms were fed with equal amount of E. coli expressing double-stranded RNA targeted to indicated genes, or mock. Feeding was begun at the L4 stage.…”
Section: Identification Of F57f44 As a Major Glycoprotein Counterparsupporting
confidence: 92%
“…However, this strategy is easily adaptable to other proteins (e.g. Figure 3 D) as well, and similar strategies have been used by us and other investigators, in a range of organisms and for different applications (Jansen et al, 2007;Erhardt et al, 2008;McMurray and Thorner, 2008;Maduzia et al, 2010;Bojkowska et al, 2011;Campos et al, 2011;Dunleavy et al, 2011;Silva et al, in press; also reviewed in O' Hare et al, 2007). We will describe two typical types of SNAP-labeling strategies: Pulse-Chase (Basic Protocol 1) and Quench-Chase-Pulse (Basic Protocol 2), which allow for the analysis of old and new protein pools, respectively.…”
Section: Introductionmentioning
confidence: 82%
“…Endogenous glycoproteins that bind to LEC-6 have been reported previously. [20][21][22][23] We recently suggested that F57F4.4 is the major glycoprotein ligand for LEC-6.…”
Section: Discussionmentioning
confidence: 99%